(untitled) (Research in Agriculture Livestock and Fisheries, 2024)
Blood is an important tool for accurate diagnosis of disease, forensic investigation, and hematological analysis. However this phenomenon can be thwarted occasionally if appropriate anticoagulant with storage times is not maintained properly. This research aims to compare and explore the effect of anticoagulants (such as ethylene diamine tetra acetic acid and heparin) and storage time on the hematological parameters in indigenous goats. Twenty goats were enrolled and raised for this purpose. Bloods were collected into two different tubes containing EDTA and heparin and analyzed immediately to evaluate the basal value. All tubes were divided into two aliquots and stored at 4°C and 25°C and were analyzed again at the 24th and 48th hours of collection. The statistical analysis of this result showed that there was no significant difference (P>0.05) in the anticoagulant’s effect on the hematological parameters. RBC, Hb, PCV, MCV, MCH, MCHC, total WBC, and Platelets except ESR decreased gradually along with the storage time of up to 48 hours compared to the basal value. The hematological parameters were reduced more significantly (P<0.05) when stored at 250C rather than 4°C indicating that the parameters remain in better condition in refrigeration. The samples should be stored at 4°C rather than room temperature and be used within 24 hours because the storage time modify the analyzed results. These findings demonstrate that both of the anticoagulants (EDTA and Heparin) show reliable results, therefore it can be used to store blood samples for any diagnostic purpose. Res. Agric. Livest. Fish. Vol. 11, No. 1, April 2024: 1-10